Renal tubular dysgenesis in a case of fetus acardius amorphus - Thoeni, Cornelia; Holzer, Kerstin; Leichsenring, Jonas; Lucena Porcel, Carlota; Straub, Beate Katharina; Sinn, Peter; Elsässer, Michael; Volckmar, Anna-Lena; Schirmacher, Peter; Waldherr, Rüdiger; Lasitschka, Felix (Case reports in pathology, 2019)
Fetus acardius amorphus is a rare congenital malformation characterized by the lack of a functional heart, the presence of a bivascular umbilical cord, as well as a developed and organized skeletal system and partially organized inner organs. Fetus acardii mostly occur in multiple gestations. The pathogenesis of this entity is not clarified yet. It has been hypothesized that, although formation of anastomosing vessels between the co-twin and the anomalous embryo as well as reverse directed blood flow within the umbilical arteries of the weaker twin may allow sufficient blood flow to form rudimentary internal organs, it is insufficient to develop a fully functional heart. We had a case of fetus acardius amorphus, where we performed autopsy as well as routine histology assessment to identify different types of tissues. We showed that our fetus acardius amorphus demonstrated histomorphological features of renal tubular dysgenesis, confirmed by lack of proximal tubules, extramedullary hematopoiesis and increased number of smooth muscle actin positive vessels. This is a novel finding and has not been reported previously
Gesehen am 16.04.2020